Efektivitas Antara Hidrasi Optimal dan Aktivitas Otak pada Mahasiswa dan Pekerja: Studi Biopsikologi - Mellisa Zahra Nuraini; Nurifa Aulia Anggraeni; Rasifa Mar Atuzzulfa; Ruth Natalia Susanti (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
This study aims to explore the effectiveness of optimal hydration on brain activity and mental health in students and workers through a biopsychological approach. Five participants (three students and two workers) participated in a hydration intervention by drinking at least 8 glasses of water per day for seven days. The design used was a one-group pretest-posttest, with measurements using the PANAS (Positive Affect Negative Affect Schedule) scale and daily reflection. The results showed an increase in positive emotion scores and a decrease in negative emotion scores after the intervention was carried out in both groups. Participants' daily reflections supported these findings, although some experienced discomfort such as bloating or nausea. Biopsychologically, adequate hydration can contribute to cognitive function, emotional control, and daily productivity. This study confirms that regular drinking habits are a simple but effective strategy in improving mental health and brain function in both students and workers.